USE OF ELECTRONIC CIGARETTES BY STUDENTS IN THE HUMANITIES AT A PRIVATE UNIVERSITY IN ANÁPOLIS, GOIÁS (CIPEEX, 2025)
The use of electronic cigarettes, particularly among young people, is a public health concern. Therefore, the objective of this study was to evaluate the use of electronic cigarettes among humanities students at a private university in Anápolis, Goiás. This is an observational, descriptive quantitative study that included students enrolled in administration, international relations, law, advertising and marketing, and pedagogy programs, aged 18 or older, who signed the Free and Informed Consent Form (FICF). Data from 168 participants were analyzed, of which 34 were electronic cigarette users. The majority were female (55.8%), self-declared as white (58.8%), half were in the age group of 18 to 20 years and the other half between 21 and 24 years, and single individuals predominated (58.9%). Finally, most had a monthly income of two to three minimum wages, were employed, and had very low dependence (52.9%) on ECs. The motivations for use were varied, followed by addiction and personal preference. Additionally, it was observed that most used them at bar parties (38.2%) and in the company of others (64.7%). This study identified the nuances in EC use to develop effective awareness and risk behavior reduction strategies.
Keywords: Electronic Nicotine Delivery Systems; Humanities; Smoking